Design of eddy current testing probe for surface defect evaluation - Mohd Mawardi, Saari; Nurul A’in, Nadzri; A. M., Halil; M., Ishak; Kenji, Sakai; Toshihiko, Kiwa; Keiji, Tsukada (Universiti Malaysia Pahang, 2019)
Early detection of defects in metallic components used in infrastructure is crucial to ensure their safety and reliability. This paper presents a development of a small eddy current testing (ECT) probe for evaluation of sub-millimetre surface defects. The ECT probe is developed in a planar differential using sensitive anisotropy magnetoresistance sensors, and the signal amplification is achieved by a home-made instrumentation amplifier. The developed ECT probe is evaluated by performing phase sensitive measurement of the magnetic responses of sub-millimetre surface slits at the excitation field of 200 Hz and 10 kHz. Compared to the real component of the magnetic response, the imaginary component can be used to identify the existence and position of the slits based on the signal intensity change caused by the induced eddy current. The spatial distribution of the magnetic response measured by the ECT probe can be used to estimate the dimension of the slit. It is expected that the developed ECT probe can be utilised for assessment of sub-millimetre surface defect.